Microwave-assisted extraction of β-sitosterol from cocoa shell waste - N. H., Ibrahim; Mohd Sabri, Mahmud; Said, Nurdin (IOP Publishing, 2020)
Phytosterol from cocoa shell can be reused in food industries in order to add value of the agricultural waste. Its extraction from the cocoa shell using ethanol can be assisted by using microwave for effective heating. This study was carried out to delineate the effect of temperature, power and radiation time of the microwave onto the extraction of β-sitosterol, as the key phytosterol, from the cocoa shell of Theobroma cacao L. species using absolute ethanol. Salkowski test, IR spectra and GC-MS analyses confirmed the presence of β-sitosterol and a flame-ionization-detector gas chromatography was employed to measure its concentration. Based on the one-factor-at-a-time (OFAT) approach, the maximum yield was obtained 13% higher than the yield of conventional maceration, i.e. 3546.1 mg/100g, at the optimum values of 70°C, 500 W and 10 min. Solubility and boiling point of ethanol onto extraction at various extraction temperatures probably caused the differences.